Upaya Kesehatan Lansia Terkait Penurunan Hipertensi - Nuryati, Tati; Okvamika, Dian Haerani; Fitri, Fauziatil; Mas’amah, Mas’amah; Hafsah, Eha; Anugrahini, Dwi Novita (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
The aim of this research is to provide education to increase the knowledge, attitudes and behavior of the elderly regarding the prevention and treatment of hypertension in the elderly using counseling methods. This counseling method is in the form of data processing results from a pre-test questionnaire and a post-test questionnaire which shows that the results of the post-test questionnaire are better than the pre-test questionnaire. This means that people's knowledge after the extension rose higher than before the extension.